Blood culture positivity in patients with acute appendicitis: A propensity score-matched prospective cohort study - Sula Sami; Han Tatu T; Marttila Harri; Haijanen Jussi; Löyttyniemi Eliisa; Sippola Suvi; Grönroos Juha; Hakanen Antti J; Salminen Paulina (SAGE PUBLICATIONS LTD, 2022)
Background and objective: The prevalence of bacteremia in acute appendicitis is unknown. We aimed to assess prevalence and predictive factors of bacteremia in adult patients with appendicitis.
Methods: In this prospective propensity score-matched cohort study, patients were recruited as part of one single-center prospective observational study assessing appendicitis microbiology in concurrence with two randomized controlled trials on non-operative treatment of uncomplicated acute appendicitis. All patients evaluated for enrollment in these three trials between April 2017 and December 2018 with both a confirmed diagnosis of appendicitis and available blood culture on admission were included in this study. Potential predictive factors of bacteremia (age, sex, body mass index (BMI), body temperature, C-reactive protein (CRP), leukocyte count, comorbidities, symptom duration, and appendicitis severity) were assessed. Prevalence of bacteremia was determined by all available blood cultures followed by propensity score matching using sex, age, BMI, CRP, leukocyte count, and body temperature of the patients without available blood culture.
Results: Out of the 815 patients with appendicitis, 271 patients had available blood culture and the prevalence of bacteremia was 12% (n = 33). Based on propensity score estimation, the prevalence of bacteremia in the whole prospective appendicitis cohort was 11.1%. Bacteremia was significantly more frequent in complicated acute appendicitis (15%; 29/189) compared with uncomplicated acute appendicitis (5%; 4/82) (p = 0.015). Male sex (p = 0.024) and higher body temperature (p = 0.0044) were associated with bacteremia.
Conclusions: Estimated prevalence of bacteremia in patients with acute appendicitis was 11.1%. Complicated appendicitis, male sex, and higher body temperature were associated with bacteremia in acute appendicitis.